Contractual Design with Correlated Information Under Limited Liability - Dominique M. Demougin; Devon A. Garvie (Queen's University, Department of Economics, 1991)
We examine contractual design in a principal-agent model under two forms of limited liability: non-negative constraints on the transfer payments to and the profits of the agent. We show that when limited liability is a binding constraint the principal cannot implement the first-best solution and the agent earns rents from private information. Limited liability is a binding constraint in the non-negative transfers model only when a signal is insufficiently responsive to type (inelastic). Further, as the production rule and profits are continuous in the type elasticity of the signal density function, the level of inefficiency is less than that which obtains with no signal. If a signal is sufficiently responsive to type (elastic) in this environment, then the principal can implement the first-best allocation and the value of the agent's private information is zero.
Keywords: 330